Let the TV on! Audience Behaviour Patterns during ‘First Wave’ of Covid-19 in the Czech Republic - Holešovský, Tomáš; Ketman, Jakub; Páral, Karel (Information & Media, 2023)
While most media research on the Covid-19 pandemic focuses on misinformation or polarisation of society, we find a niche in what strategies mass audiences chose to adopt when receiving the news. We addressed this very question immediately at the beginning of the pandemic in the Czech Republic in 2020, choosing a quantitative method and apply it on a representative sample of the Czech population according to standard quota sampling parameters. The specificities of the Czech Republic, as one of the most affected countries and holding the primacy with the highest number of deaths from Covid-19 per population in the world, played an important role in the selection of news. Our research identified four basic groups of recipients: Concerned, Careful, Sceptical, and Detached. Research in Germany (Wolling, Schumann & Arlt, 2020), for example, has found similar classifications. Another important finding was the audience’s preferences in terms of the use of different types of media, with our respondents being completely dominated by television as the primary source of information. Other key finding is that audiences felt overwhelmed by news of the pandemic, which implies challenges for further research but especially for journalistic practice.